Splenectomy with Portoazygous Disconnection for Correction of Systemic Hemodynamic Disorders in Hepatic Cirrhosis Patients with Portal Hypertension: A Prospective Single-Center Cohort Study - Zeng, Dao-Bing (Can J Gastroenterol Hepatol, 2020)
OBJECTIVE: To investigate the effect of splenectomy for correction of systemic hemodynamic disorders in hepatic cirrhosis patients with portal hypertension. METHODS: Hepatic cirrhosis patients with portal hypertension were enrolled from April 2015 to July 2018. Systemic hemodynamic parameters (heart rate, mean arterial pressure (MAP), cardiac output, and total peripheral vascular resistance (TPR)) were prospectively measured at baseline and 1 week, 1, 3, and 6 months, and 1, 2, and 3 years postoperatively. Paired analysis was conducted. RESULTS: Sixty-nine patients were eligible, and 55 (79.7%) cases had a history of upper gastrointestinal bleeding. Child–Pugh classification was grade A in 41 (59.4%) cases, grade B in 26 (37.7%) cases, and grade C in 2 (2.9%) cases. The heart rate was significantly higher at 1 week postoperatively versus the baseline (P < 0.001). Meanwhile, the heart rate was significantly lower from 3 months to 2 years postoperatively versus the baseline (P < 0.05). The MAP was significantly higher at 6 months to 2 years postoperatively versus the baseline (P < 0.05). At 1 month postoperatively and 6 months to 2 years, the cardiac output was significantly lower versus the baseline (P < 0.05). At 1 month postoperatively and 6 months to 2 years, the TPR was significantly higher versus the baseline (P < 0.05). CONCLUSION: Splenectomy corrects systemic hemodynamic disorder in hepatic cirrhosis patients with portal hypertension, and the effect is rapid and durable.